Teknik Pencucian Mempengaruhi Angka Kuman Pada Peralatan Makan: Studi Literatur - Aulia Mulya; Rahmawati Rahmawati; Erminawati Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Tableware is one of the most important factors in the spread of disease, the non-hygiene and microorganism’s container Tableware can spread disease through food. Therefore, the washing process with the right method is very important in efforts to reduce bacterial numbers, especially in tableware. The purpose of this research was to know the correlation between tableware washing method in food processing place with the bacterial numbers in tableware. This research was an analytical research with literature study method using 5 journals studied. The results of the 5 journals studied showed that 35.5% of 121 TPMs (food processing place) carried out tableware washing with inappropriate techniques 56,9% of 258 observed tableware sample contain ineligible microorganisms. 3 of the studied journal claimed there was no significant correlation between washing technic variable with the bacterial numbers variable in tableware as the P value = 1000 while 2 other studied journal claimed there was a correlation between washing technic variable with the bacterial numbers variable in tableware. Based on the research results from the studied journal, efforts can be made to pay more attention to hygiene and not ignoring the proper washing techniques as suggested, such as flushing, rinsing and sanitizing to avoid the bacterial numbers that exceed the standard.